2004
DOI: 10.1086/424016
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychosis among Patients with Severe Acute Respiratory Syndrome: A Case-Control Study

Abstract: We observed that a number of patients with severe acute respiratory syndrome (SARS) developed affective psychosis during the acute phase of their illness. We reviewed all SARS-related psychiatric consultations in Hong Kong and investigated the risk factors for psychosis among patients with SARS in a matched case-control study. Patients with SARS-related psychosis received higher total doses of steroids and had higher rates of family history of psychiatric illness. The findings of the present study suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
118
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 4 publications
3
118
0
1
Order By: Relevance
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress [150] and mood disturbances [151]. Furthermore, steroid toxicity, personal vulnerability and psychosocial stressors might have contributed to the development of psychosis in some patients [152]. Longer term follow-up is needed to assess if these deficits are persistent.…”
Section: Long-term Outcomementioning
confidence: 99%
“…The results are not surprising as, in addition to the physical impairment, the long period of isolation and extreme uncertainty during the SARS illness had created enormous psychological stress [150] and mood disturbances [151]. Furthermore, steroid toxicity, personal vulnerability and psychosocial stressors might have contributed to the development of psychosis in some patients [152]. Longer term follow-up is needed to assess if these deficits are persistent.…”
Section: Long-term Outcomementioning
confidence: 99%
“…Brown and associates [2] and Lee and associates [17] report higher rates of psychiatric episodes where there is family history of psychiatric illness. Chau and Mok [3] describe a history of anxiety disorders as a predictive factor for corticosteroid psychosis and Brown and associates [2] describe posttraumatic stress disorder as increasing the likelihood of mood disturbance during corticosteroid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 The first was a case-control study of SARS patients with (n=15) and without (n=30) SARS-related psychosis; all were given corticosteroid treatment, but those who developed psychosis were given a higher cumulative dose than those who did not (10 975 mg hydrocortisone equivalent vs 6780 mg; p=0·017). 6 The second was a randomised controlled trial of 16 patients with SARS who were not critically ill; the nine patients who were given hydrocortisone (mean 4·8 days [95% CI 4·1-5·5] since fever onset) had greater viraemia in the second and third weeks after infection than those who were given 0·9% saline control. 5 The remaining two studies reported diabetes and avascular necrosis as complications associated with corticosteroid treatment.…”
mentioning
confidence: 99%